Statehood as political community : international law and the emergence of new states / Alex Green, University of York. - Green, Alex, 1988- (ASIL studies in international legal theory., 2024)
Alex Green argues that states arise under contemporary international law only when two abstract conditions are fulfilled. First, emerging states must constitute 'genuine political communities': collectives within which particular kinds of ethically valuable behaviour are possible. Second, such communities must emerge in a manner consistent with the ethical importance of individual political action. This uniquely 'Grotian' theory of state creation provides a clear legal framework comprising four factual 'antecedents' and five procedural principles, rendering the law of statehood both coherent and normatively attractive.